PERSPEKTIF ELABORATION LIKELIHOOD MODEL (ELM) DALAM PENGEMASAN INFORMASI KALENDER TANAM DIKALANGAN PENYULUH PERTANIAN DI KABUPATEN PANDEGLANG PROVINSI BANTEN - ARI SURACHMANTO; PRAHASTIWI UTARI; ANDRE RAHMANTO (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2019)
This study aims to see how agricultural extension workers in Pandeglang district design a message on Plant Calendar from the Elaboration Likelihood Model Theory. The method used in this research is descriptive qualitative with case study approach. The results showed that agricultural extension workers in Pandeglang district have applied empathy logic to the farmers, by responding to how the farmers in the region got and processed information about planting calendar. The peasants unconsciously mempraksiskan ELM theory which then responded empathetically by agricultural extension with a strong argument based on data. The conclusions of this research are (1) to compile information based on accurate data, in order to manifest a message based on fact, concerning the content or content of extension material, (2) to animate the speech in a strong argumentation frame by selecting and sorting the word, diction and other language elements, (3) participatory logic. This logic can be a strong argumentation by plunging into the fields, so that the distance between the farmers.